Problematika Perkuliahan Analisis Real - Mutiara Arafah Nst; Rusi Ulfa Hasanah; Aldy Wijaya (Jurnal Mahasiswa Kreatif, 2024)
The purpose of this article is to highlight various problems commonly faced by undergraduate students studying mathematics and undergraduate students studying mathematics education in real analysis classes. The Real Analysis course aims to teach students how to: a) understand the fundamentals of mathematical analysis, especially those related to numbers, rows, functions, limits, and derivatives; and b) be able to reason logically and thoroughly and methodically express the conclusions of their reasoning in writing. One of the topics that students studying mathematics and mathematics education programs often think about is real analysis. The author of this study discusses some substitute approaches that can be recommended to assist students in adjusting to face-to-face analysis courses. Lecturers can also attempt to improve quality by implementing various interventions, practicing Lesson Study learning, using RME techniques, and creating a real analysis textbook.